2022
DOI: 10.3390/su14095486
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impacts of Behavioural-Change Interventions and COVID-19 on the Food-Waste-Generation Behaviours of Catered Students in the UK and India

Abstract: A food-waste initiative was conducted at two university canteens in the UK and India to examine food-waste attitudes and opportunities for food-waste reduction. Interventions were carried out to reduce food waste in both canteens. In the Indian canteen, postintervention data also included COVID-19-related changes, such as a change from self-service to table service, as well as reduced menu choices and an improved estimation of the number of students requiring meals. Surveys and focus groups were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Another action proposed by Grech et al ( 2020 ) is related to packages, minimizing their use, and recycling them. Following this idea, the trayless initiative is an infrastructural action to reduce FW, plus a cultural one (Davison et al, 2022 ). Concerning reducing FW, Grech et al ( 2020 ) and other authors suggest that canteens could be reducing plate and utensil sizes, go trayless, adjust quantities of food made available to trends of consumption, menu options (focusing on the reduction of animal-based products availability, and inclusion of local and seasonal products that prioritize fresh and minimizes consumption of processed foods), catering styles (table service placing self-service buffet), adoption of an online prebooking meal system, development of digital applications for continuous FW monitoring, composting, and donations (Cavazos et al, 2023 ; Davison et al, 2022 ; Martinho et al, 2022 ; Musicus et al, 2022 ; Zhang & Kwon, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another action proposed by Grech et al ( 2020 ) is related to packages, minimizing their use, and recycling them. Following this idea, the trayless initiative is an infrastructural action to reduce FW, plus a cultural one (Davison et al, 2022 ). Concerning reducing FW, Grech et al ( 2020 ) and other authors suggest that canteens could be reducing plate and utensil sizes, go trayless, adjust quantities of food made available to trends of consumption, menu options (focusing on the reduction of animal-based products availability, and inclusion of local and seasonal products that prioritize fresh and minimizes consumption of processed foods), catering styles (table service placing self-service buffet), adoption of an online prebooking meal system, development of digital applications for continuous FW monitoring, composting, and donations (Cavazos et al, 2023 ; Davison et al, 2022 ; Martinho et al, 2022 ; Musicus et al, 2022 ; Zhang & Kwon, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors described the implementation, in some ‘target areas’ like ethical procurement and sustainable food consumption strategies, to change students’ behavior, in line with the cultural differences and strategies that educate students and the university community about FW reduction. Governments and universities aimed to embed sustainability into institutional activities such as teaching and research, or by encouraging freshmen students to study sustainability, collaborating with the community, staff development, branding, reducing carbon emissions, and transforming campuses in all activities and resources (water, grounds, FW, procurement and purchasing) in a perennial commitment to sustainability (Cavazos et al, 2023 ; Davison et al, 2022 ; Grech et al, 2020 ; Martinho et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some are actively involved in sustainable practices; a small group remain sceptical. Davison et al (2022) explore the impact of behavioural change interventions to reduce food waste in two universities from India and UK. They found that interventions have greater impact in India.…”
Section: Studies On Students and Methodologymentioning
confidence: 99%
“…A difficulty arises here. Nudges are sensitive to culture (Bovens, 2010;Davison et al, 2022); pro-environment behaviour is demographically dependent (Schultz et al, 1995;Fisher et al, 2012). Studies propose education as an instrument towards sustainability (e.g., Leal Filho et al, 2019;Salazar et al, 2022).…”
Section: Recycling and Nudgesmentioning
confidence: 99%
See 1 more Smart Citation